Pengaruh Pembiasaan Sholat Dhuha Berjamaah terhadap Akhlak Siswa Kelas VII MTS Mathla’ul Anwar Tanah Sareal Bogor - Ismaya Wardati Basimah; Suhendra; Amran (Jurnal Dirosah Islamiyah, 2024)
The purpose of this study was to determine whether there is an effect of habituation of dhuha prayer in congregation on the morals of seventh grade students at MTs Mathla'ul Anwar Tanah Sareal Bogor. The population in this study included all VII grade students of MTs Mathla'ul Anwar Tanah Sareal Bogor consisting of 4 classes with a total of 115 students. This study uses quantitative methods where the data collection process is carried out by distributing research questionnaires to 53 seventh grade students at MTs Mathla'ul Anwar Tanah Sareal Bogor. The results showed that: (1) the habituation of dhuha prayer in congregation obtained an average of 62 these results indicate that the habituation of dhuha prayer in congregation is included in the good category. (2) the morals of seventh grade students obtained an average score of 49, it shows that the morals of seventh grade students are included in the good category. (3) the results of the simple linear regression test 0.000 <0.05 show that there is a positive and significant effect of habituation of dhuha prayers in congregation on the morals of seventh grade students at MTs Mathla'ul Anwar, so Ha is accepted and Ho is rejected. Therefore, if you want to shape students' morals for the better, one of the things that must be considered is the habituation of dhuha prayers in congregation.